STRATEGI KEBIJAKAN PEMERINTAH TENTANG PENDIDIKAN DASAR DAN MENENGAH GRATIS DI BANTEN - Purnama, Barkah; Djunaidy, Bryan Pratama (Yayasan Amanah Nur Aman, 2025)
This study discusses the policy strategies of the Banten Provincial Government in implementing free education programs at the high school/vocational school level. The primary focus of the study is to analyze the government's efforts to improve access to education and reduce dropout rates, particularly during the transition from junior high school to senior high school. However, in its implementation, the program still faces various challenges, such as budget constraints, inadequate educational infrastructure, and disparities in the quality of educational services between urban and rural areas. Additionally, affirmative policies for vulnerable groups, such as poor families and people with disabilities, are still suboptimal, while the quality and distribution of educators are not evenly distributed across the Banten region. This study uses a qualitative approach with in-depth interviews conducted at the Banten Provincial Education Office (KP3B Serang). The research findings recommend the need for improved inter-institutional coordination, equitable distribution of human resources, and accelerated development of educational facilities in underdeveloped areas such as Lebak and Pandeglang. With a more adaptive approach to local needs, this free education policy is expected to promote equitable access and improved educational quality in Banten Province, thereby fostering the development of superior and competitive human resources.